Older Adults More Likely to Discuss Advance Care Plans With an Attorney Than With a Physician - Bern-Klug, Mercedes (Gerontol Geriatr Med, 2017)
Adults are encouraged to discuss their end-of-life health care preferences so that their wishes will be known and hopefully honored. The purpose of this study was to determine with whom older adults had communicated their future health care wishes and the extent to which respondents themselves were serving as a surrogate decision maker. Results from the cross-sectional online survey with 294 persons aged 50 and older reveal that among the married, over 80% had a discussion with their spouse and among those with an adult child, close to two thirds (64%) had. Over a third had discussed preferences with an attorney and 23% with a physician. Close to half were currently serving as a surrogate decision maker or had been asked to and had signed papers to formalize their role. 18% did not think that they were a surrogate but were not sure. More education is needed to emphasize the importance of advance care planning with a medical professional, especially for patients with advanced chronic illness. More education and research about the role of surrogate medical decision makers is called for.